2019
DOI: 10.1016/j.ophtha.2018.10.032
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Binocular Dig Rush Game Treatment for Amblyopia in Children Aged 7 to 12 Years

Abstract: Purpose: To compare visual acuity (VA) improvement in children aged 7 to 12 years with amblyopia treated with a binocular iPad ® game plus continued spectacle correction versus continued spectacle correction alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 18 publications
(8 reference statements)
2
99
2
2
Order By: Relevance
“…A variety of binocular, dichoptic, and virtual reality perceptual learning tasks and games have been developed as potential treatments for amblyopia. [17][18][19][20][21][22] Some authors have hypothesized that action video games may provide the best approach because they are not only highly engaging, requiring attention to identify and track potential targets, but they also trigger arousal via time constraints, decision making, and task performance and provide immediate feedback on success or failure. 22,33 The current study provides evidence for visual acuity improvement as a result of passive exposure to dichoptic contrast-rebalanced video content, in the absence of the requirement to perform any task and without any feedback.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of binocular, dichoptic, and virtual reality perceptual learning tasks and games have been developed as potential treatments for amblyopia. [17][18][19][20][21][22] Some authors have hypothesized that action video games may provide the best approach because they are not only highly engaging, requiring attention to identify and track potential targets, but they also trigger arousal via time constraints, decision making, and task performance and provide immediate feedback on success or failure. 22,33 The current study provides evidence for visual acuity improvement as a result of passive exposure to dichoptic contrast-rebalanced video content, in the absence of the requirement to perform any task and without any feedback.…”
Section: Discussionmentioning
confidence: 99%
“…Binocular amblyopia treatments promote simultaneous use of both eyes by rebalancing the strength of each eye's image with high-contrast or high-luminance input to the amblyopic eye and low-contrast or lowluminance input to the fellow eye. [17][18][19][20][21][22] Currently, most binocular treatments require active participation by the amblyopic child: playing a game or performing a repetitive psychophysical task. We recently reported our results of a passive binocular treatment, where the subject watches contrast-rebalanced dichoptic movies in which reciprocal blob-shaped parts of the image are presented to each eye to promote binocular combination.…”
mentioning
confidence: 99%
“… 20 As well as limiting stereopsis by preventing sensory fusion, 21 the role that suppression plays in causing or limiting amblyopia recovery is yet to be fully determined. Novel treatments for amblyopia are aimed at reducing suppression of the amblyopic visual pathway to improve binocularity 22 25 ; however, the relative contribution of interocular differences in visual acuity and depth of suppression in determining the limit of stereoacuity is unclear. For example, it has been believed for some time that amblyopia (reduced acuity in one eye) is the primary problem and loss of binocularity, the consequence.…”
mentioning
confidence: 99%
“…Most recently, in 2019, PEDIG published the results of its study of Dig Rush, which was found to be a more engaging game for children. 31 This report detailed the results of an older cohort, ages 7 to 13 years, who were randomized to 1 hour of daily dichoptic game play (Dig Rush, n ¼ 69) or continued spectacle wear (n ¼ 69) for 8 weeks. The VA results were similar to PEDIG's previous studies; after adjusting for baseline VA, the mean amblyopic eye letter score at 8 weeks improved by 2.3 letters (95% CI, 0.7e3.9 letters) for the dichoptic group and 2.4 letters (95% CI, 0.8e4.0 letters) for the control group.…”
Section: Amblyopic Eye Visual Acuitymentioning
confidence: 99%